2020
DOI: 10.1002/lary.29217
|View full text |Cite
|
Sign up to set email alerts
|

Tubed Supraglottic Laryngeal Closure to Treat Chronic Aspiration After Radiotherapy for Head and Neck Cancer

Abstract: Objectives/Hypothesis: To evaluate the long-term swallowing outcomes after surgical treatment for chronic aspiration in patients treated with radiotherapy for head and neck cancer. Study Design: This was a retrospective study. Methods: The data of patients who underwent radiotherapy for head and neck cancer and who subsequently required a laryngectomy or a tubed supraglottic laryngeal closure (TSLC) for recurrent aspiration pneumonia between 2004 and 2017 were retrieved from a tertiary referral hospital dyspha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One TSLC patient who had a good postoperative voice and swallowing function suffered from social anxiety related to the tracheostomy tube. The patient was eventually decannulated after undergoing an adequate transoral carbon dioxide laser reopening of the tubed supraglottis 14 . This demonstrated that a TSLC is a reversible procedure that preserves the larynx and allows for natural phonation and that can be considered an alternative to a laryngectomy for the control of chronic aspiration, especially for those patients who are reluctant to lose their larynx.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One TSLC patient who had a good postoperative voice and swallowing function suffered from social anxiety related to the tracheostomy tube. The patient was eventually decannulated after undergoing an adequate transoral carbon dioxide laser reopening of the tubed supraglottis 14 . This demonstrated that a TSLC is a reversible procedure that preserves the larynx and allows for natural phonation and that can be considered an alternative to a laryngectomy for the control of chronic aspiration, especially for those patients who are reluctant to lose their larynx.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported on the efficacy of a TSLC to control chronic aspiration in post‐irradiated NPC patients 14 . Of the 17 patients in that series who required surgery for chronic aspiration secondary to radiotherapy for head and neck cancer, two underwent a laryngectomy and 15 a TSLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have examined APS, [9][10][11][12][13][14][15][16][17]23 they have investigated a single surgical technique or a specific disease, which is inadequate for determining the benefits and risks of APS. Here, we included 100 patients, which is, to our knowledge, the largest sample size reported in APS-related publications to date.…”
Section: Discussionmentioning
confidence: 99%
“…Tubed supraglottic closure has been recently described, with encouraging results. 633 Laryngeal voice in the presence of a tracheostomy can be achieved whilst minimising the aspiration risk by reducing the supraglottic aperture.…”
Section: Other Surgical Interventionsmentioning
confidence: 99%